QARAQALPAQ TILINDE QÍZÍL LEKSEMASÍNÍŃ MÁNILERI - Sankibaeva, R. (SCIENCE and SOCIETY, 2022)
The article deals with the meanings of the lexeme Red, denoting colour, in the Karakalpak language, its semantics and application. It has been shown that it expresses not only colour, but can also be used in other senses.